Cultural maintenance and Chetti identity in the Melaka Chetti (Chetti) community, Kampung Chetti, Gajah Berang, Melaka (International Journal of Language, Literacy and Translation, 2025)
This paper reports on cultural maintenance and Chetti identity in the Melaka Chetti (or Chetti) community at Kampung Chetti, Gajah Berang, Melaka. The study examines two very important Chetti cultural practices at Kampung Chetti and how community members identify themselves as Chetti, particularly in the prospect of impending assimilation into the larger Indian community due to exogamy. Participant observation and video documentation of the Bhogi Parchu and Mengammay at Kampung Chetti reveal that these annual cultural practices serve as vital platforms for the manifestation and maintenance of Chetti culture. Interviews conducted with senior and younger members of the community provided views and insights on Chetti culture, identity, and assimilation. The older generations view identity as a ‘brought along’ predetermined variable, while for the younger Chettis, their multiple, fluid identities are co-constructed, negotiated and ‘brought about’ in different social contexts. The older generations are more concerned and wary of assimilation and extinction. Three factors (religion, cultural maintenance, Kampong Chetti) may determine the community’s survival; however, in the event of assimilation into the larger Indian community, a less distinct Chetti community may emerge. It would be a significant loss to our multicultural mosaic if this distinct Peranakan Indian community ceases to exist; nevertheless, given recognition as a ‘heritage community’ by the Melaka government and as a ‘symbol of national unity’ in the recent Peranakan Festival 2023, the Chetti community may ultimately strive to survive. In conclusion, the Bhogi Parchu and Mengammay practices at Kampung Chetti not only play a pivotal part in carefully preserving the complex tapestry of Chetti cultural tradition but also contribute significantly to the dynamic and ongoing construction of a resilient identity among its members.